Nilai-Nilai Transformatif Salat: Studi Analisis QS. Al-Mu'minun Ayat 1-2 - Navisah Al Ainiyah; M. Yunus Abu Bakar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the transformative values of prayer based on QS. Al-Mu'minun verses 1-2, which emphasize the importance of solemnity in the practice of worship. Prayer, as a fundamental pillar of Islam, serves not only as a ritual obligation, but also as a means to achieve spiritual and moral peace. In the modern context and the challenges of the digital era, this research explores how solemnity in prayer can shape the character and social interactions of Muslims. Using a literature study approach, this research collects and analyzes various sources to understand the impact of prayer on the formation of positive attitudes such as patience, honesty, and caring, which contribute to the creation of harmony in society. The results of the study show that the solemnity of prayer plays an important role in the formation of such positive attitudes, which are essential in facing contemporary social challenges. Amidst the challenges of the digital age that often distract from spiritual values, the practice of prayer faces various distractions that can reduce the quality of worship. Hence, innovative solutions such as prayer reminder apps and the establishment of supportive communities are essential for enhancing solemnity. The study concludes that prayer has significant transformative values that can be implemented in social life, and emphasizes the need to utilize technology wisely to strengthen the practice of worship and its relevance in the modern context. By understanding these values, it is hoped that Muslims will be able to better appreciate prayer in a modern context, thereby addressing contemporary social challenges and strengthening relationships between individuals in society.